Logistics Innovation Mechanisms of Agricultural Competitiveness Development in Spatial Economic Transformation - Voloshchuk, Maksym; Sherstiuk, Oleksandr; Petrushov, Vasyl; Burtsev, Oleksandr (Dr. Viktor Koval, 2026)
Background. The study examines the transformation of the logistics component of enterprises’ competitiveness in the agricultural sector of Ukraine under conditions of spatial economic changes driven by military events and the restructuring of export infrastructure. The relevance of analysing export logistics channels stems from their decisive role in the resilience of agricultural production given changes in transport route configurations, increased risks, and the need to adapt to new geo-economic conditions. Purpose. This study aims to analyse the impact of the structure and diversification of export logistics channels on the competitiveness of the agricultural sector and develop an integrated approach to measure the logistics component of comprehensive performance. Findings. The study employs statistical, comparative analysis methods, and an index approach to assess the structure of logistics flows. The dynamics of agricultural production indices for 2014–2024, the structure of export logistic flows, and the share of transport modes in agricultural exports are also considered. The diversification index of logistics channels was calculated, reflecting the transition from a highly concentrated logistics structure to a more diversified one. A Logistics Competitiveness Index was also constructed, which integrates export volume, degree of diversification, and the share of alternative routes. The results demonstrated a transition from a mono-channel maritime model in 2021 to a diversified configuration in 2022–2023, which performed an adaptive function and contributed to the recovery of export activity. In 2024, the export volume increased to 70 million tonnes, 12.9% more than in 2023 (62 million tonnes). However, this occurred against the background of a partial return to a more concentrated structure of logistics flows, driven by the restoration of the maritime transport channel’s role. Implications. The competitiveness of agricultural enterprises in a transformed economic space is determined not only by the scale of exports but also by the structural balance of transport channels. Maintaining a multichannel logistics model is considered a key element of logistics innovation mechanisms to ensure resilience and long-term competitive advantage.